2006
DOI: 10.1111/j.1440-1681.2006.04350.x
|View full text |Cite
|
Sign up to set email alerts
|

THE CATECHOLAMINE–β‐ADRENORECEPTOR–cAMP SYSTEM AND PREDICTION OF CARDIOVASCULAR EVENTS IN HYPERTENSION

Abstract: Although the importance of elevated circulating plasma catecholamines on cardiac structural and functional remodelling of hypertension is well documented, it is unclear whether the catecholamine-beta-adrenoreceptor (beta AR)-cAMP system can predict different cardiovascular events. 2. A total of 601 identified hypertensive patients with baseline and follow-up plasma levels of noradrenaline (NA) and adrenaline (Adr), lymphocyte beta AR density (B(max)) and intra-lymphocyte cAMP levels in peripheral blood (last e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Nonetheless, venous norepinephrine concentrations have been used widely as an indirect marker of global sympathetic tone. They are correlated with more specific markers of sympathetic activity such as muscle sympathetic nerve activity (MSNA) at rest [43] and increase similarly after a reduction in blood pressure [44,45], have strong heritability [4], and in longitudinal studies predict cardiovascular morbidity in both healthy subjects [46] and patients with hypertension [47] or congestive heart failure [48,49]. Additionally, we studied subjects at rest, thus minimizing the confounding effect of changes in forearm norepinephrine release and of large differences in catecholamine clearance secondary to altered blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, venous norepinephrine concentrations have been used widely as an indirect marker of global sympathetic tone. They are correlated with more specific markers of sympathetic activity such as muscle sympathetic nerve activity (MSNA) at rest [43] and increase similarly after a reduction in blood pressure [44,45], have strong heritability [4], and in longitudinal studies predict cardiovascular morbidity in both healthy subjects [46] and patients with hypertension [47] or congestive heart failure [48,49]. Additionally, we studied subjects at rest, thus minimizing the confounding effect of changes in forearm norepinephrine release and of large differences in catecholamine clearance secondary to altered blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to GRK2, immune cells also express GRKs 3, 5, and 6 [ 68 , 69 , 70 ], but these GRKs are less well studied than GRK2. Down-regulation and desensitization of the β 2 -AR is observed in many diseases where net SNS firing rate (activity) is chronically elevated and robust/chronic inflammation ensues, including hypertension [ 71 ], sepsis [ 72 , 73 , 74 ], rheumatoid arthritis (RA) [ 75 , 76 , 77 ], and asthma [ 78 , 79 , 80 ]. For hypertension, changes in lymphocyte β 2 -AR density and poorer responsiveness are significant predictors of cardiovascular mortality and myocardial infarction [ 71 ].…”
Section: Canonical Intracellular Signaling By β 2 mentioning
confidence: 99%
“…Coronary heart disease accounts for more than 40% of cardiovascular deaths and its most serious form, acute myocardial infarction (AMI), is the principal cause of chronic heart failure 1 . Elevated catecholamines are known risk factors for a cardiovascular event and the synthetic catecholamine, isoprenaline has been used for about a half a century for inducing AMI and subsequent heart failure in small laboratory animals [7][8][9][10] . In our previous study, we found in a very small number of animals some correlations among various parameters in healthy and AMIinduced animals 10 .…”
Section: Introductionmentioning
confidence: 99%